Bounding and Binding: Trajectories of Community-Organization Emergence Following a Major Disruption - Williams, Trenton Alma; Shepherd, Dean A. (Organization Science, 2021)
An important and underexamined topic in the growing literature on community-embedded organizing concerns situations in which dramatic shifts in the environment require the time-sensitive re-establishment of both communities and organizations to address urgent needs. We conduct a qualitative study of emergent community-organization trajectories in the aftermath of the 2010 Haiti earthquake and explore differences in the processes and interactions between emerging organizations and communities. Despite all organizations in our data facing the same external shock, they differed in how they interpreted the nature of crisis-induced voids, established boundaries to build and organize communities, and created connections to bind themselves to their communities. We compare and contrast these differences to reveal three trajectories of community-organization emergence, explain why these trajectories initially formed in the ways they did, and identify unique mechanisms that led to these trajectories’ divergence. Our findings contribute to the literature on community-embedded organizing by demonstrating how organizations re-establish communities while simultaneously emerging within those communities.